2022
DOI: 10.2147/prbm.s373287
|View full text |Cite
|
Sign up to set email alerts
|

Capability, Opportunity, Motivation, and Hand Hygiene Behavior in Healthcare Workers: A Structural Equation Modeling

Abstract: Background Hand hygiene among healthcare workers is the leading measure to reduce healthcare-associated infections. However, hand hygiene behavior is complex and not readily understood. This study aimed to identify the determinants and the underlying mechanism of hand hygiene behavior based on the capability, opportunity, motivation-behavior model. Methods A self-constructed questionnaire survey was conducted among healthcare workers in Chongqing, China. Capability, opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The COM-B questionnaire has been applied in several studies since its development by Lydon et al in 2019 [14e20]. However, only Zheng et al distributed and analysed the questionnaire in a similar way and setting as in the present study [17]. They distributed the COM-B questionnaire among 499 HCWs, and reported that opportunity and motivation directly affected hand hygiene behaviour [17].…”
Section: Discussionmentioning
confidence: 77%
“…The COM-B questionnaire has been applied in several studies since its development by Lydon et al in 2019 [14e20]. However, only Zheng et al distributed and analysed the questionnaire in a similar way and setting as in the present study [17]. They distributed the COM-B questionnaire among 499 HCWs, and reported that opportunity and motivation directly affected hand hygiene behaviour [17].…”
Section: Discussionmentioning
confidence: 77%
“…This gender disparity aligns with previous research conducted by Chinese scholars in the same domain. 10 , 11 In terms of age groups, doctors aged 41–50 years exhibited the highest qualification rate for hand disinfection at 91.67%. Following closely were doctors aged 31–40 years, with a rate of 65.22%, and doctors aged ≤ 30 years, with a rate of 65.00%.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng and colleagues showed that the underlying mechanism of hand hygiene behavior among HCWs is based on the capability, opportunity, and motivation-behavior model. Their study found that to improve hand hygiene behavior, more efforts should focus on resource provision and hand hygiene motivation enhancement [ 39 , 66 ]. Therefore, to improve hand hygiene habits, we need strategies that not only increase knowledge but also positively affect attitudes and views.…”
Section: Discussionmentioning
confidence: 99%